Faktor-Faktor Yang Berhubungan Dengan Perilaku Kerja Karyawan Penderita Aging Disease Di PT Holcim Indonesia Tbk Cilacap Plant - Chairunnisa Firaz (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Based on data Framingham Score Medical Check Up PT Holcim in 2013, that 65% of the total employees of PT Holcim Indonesia Tbk Cilacap Plant was more than 40 years old. From the results of the Medical Check Up, 80% of them detected a High Risk category, as seen from the measurement of blood sugar levels, cholesterol, and high blood plessure. The purpose of research to determine the factors associated with the employee behavior aging disease in PT Holcim Indonesia Tbk Cilacap Plant. This research using quantitative research method with cross sectional approach, with the employee’s population of the high risk of PT Holcim Indonesia Tbk Cilacap Plant viewed from the result of Medical check Up the company’s clinic with the total of 509 employees and the sample were taken as many as 75 people used method systematic random sampling. The source of the research data used the analysis univariat and bivariate by using chi-square ( the significant level 0.05 ).The result showed an employee aging disease which behaves well of 57,3%. Results of statistical tests showed no relationship between availability and infrastructure supporting employee behavior with aging disease in PT Holcim Indonesia Tbk Cilacap Plant (p=0,000). While the factors that do not relate to employee behavior aging disease is age (p=0,861), education (p=0,732), knowledge (p=0,085), attitudes (p=0,347), family support (p=0,618), support a co-worker (0,843), and support health workers (p=0,071). The effort that needs to be done is the monitoring of the health conditionof employees with aging disease by clinic companyand maximize existing infrastructure functionality such asfunction of the company cafeteria with the enactment of themandatory rules of lunch in the cafeteria and the utilization of the sports facilities with a routine sports schedules are held together.